1990
DOI: 10.3109/02699059009026164
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mild, moderate and severe closed head injury on long-term vocational status

Abstract: Survival from significant closed head injury (CHI) is frequently associated with cognitive defects, physical impairment, personality change, interpersonal difficulty and, in general, some degree of social dependence. Here we report a multidimensional assessment of quality of life of a sample of 131 male head-injury patients suffering a range of severities of insult with specific emphasis on vocational outcome. Of those patients who sustained a severe injury and were employed full-time prior to the CHI, only 55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
1
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(43 citation statements)
references
References 11 publications
0
41
1
1
Order By: Relevance
“…One reason to schedule the intervention during the chronic phase, rather than during the early phase after the stroke, is that it is not until the chronic phase, when patients try to go back to normal life and old working habits, that they become aware of their cognitive deficits [42] and may be motivated to re-train these functions.…”
Section: Discussionmentioning
confidence: 99%
“…One reason to schedule the intervention during the chronic phase, rather than during the early phase after the stroke, is that it is not until the chronic phase, when patients try to go back to normal life and old working habits, that they become aware of their cognitive deficits [42] and may be motivated to re-train these functions.…”
Section: Discussionmentioning
confidence: 99%
“…Work has always been a primary outcome variable after TBI because resumption of gainful employment is generally regarded as an important criterion of recovery in Western society (Stambrook, Moore, Peters Deviaene, & Hawryluk, 1990;Ponsford, Olver, Curran & Ng, 1995;Webb, Wrigley, Yoel & Fine, 1995). 'Employment, in reality, is one of the most telling of outcome variables after TBI as it relies upon the multi-dimensional integration of all functional areas' (Zasler, 1989, p. 332), as does all occupation.…”
Section: Introductionmentioning
confidence: 99%
“…'Employment, in reality, is one of the most telling of outcome variables after TBI as it relies upon the multi-dimensional integration of all functional areas' (Zasler, 1989, p. 332), as does all occupation. Occupational therapy recognizes the benefit of occupation as it provides structure, stability and purpose to life (Stambrook et al, 1990). However, there is tremendous societal support for the time structuring that employment provides (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies that did report a significant relationship between age at the time of the study and employment concluded that older adults tended to experience less favorable employment outcomes than younger adults, although the studies did not specify the age group in which the odds of returning to work decrease (Rao, et aI., 1990;Ruff, et aI., 1993;Stambrook, Moore, Peters, Deviaenes, & Hawryluk, 1990). …”
Section: Demographic and Life Characteristicsmentioning
confidence: 99%